The Influence Of Family Support In The Management Of Hypertension Patients - Chrismilasari, Lucia Andi; Er Unja, Ermeisi; Chrisnawati, Chrisnawati; Rachman, Aulia (Sean Institute, 2022)
Background: The family is the primary support system for the elderly in maintaining their health, especially for the elderly with hypertension, in preventing complications such as heart failure and stroke. The role of the family in elderly care is to look after or care for the elderly. The existence of family support will provide strength and create an atmosphere of belonging to each other in these family members in meeting the needs of family development. This research was conducted to see how family support for the management of hypertension patients in the city of Banjarmasin. Method: This study uses quantitative research methods with correlation analysis. Data collection tools are in the form of observation sheets and questionnaires. The research time is June 2022 to October 2022. The sample used in this study was 80 people using a purposive sampling technique. Data analysis was performed using the Chi-Square test at ɑ = 0.05. The results showed that 52.5% had good family support, 30% had sufficient knowledge about hypertension, 53.7% had a positive attitude towards treating hypertension, and 51.3% of sufferers were in the category of adherence to medication and controlling medication blood pressure. Result: The results of the chi-square test analysis on family support for knowledge about hypertension showed a p-value of 0.038, for family support for attitudes of hypertensive sufferers showed a p-value of 0.068, and for family support for patient adherence to taking medication and blood pressure control showed a p-value of 0.034. Suppose at a significant level < 0.05, there is a relationship between family support, patient knowledge about hypertension, and patient adherence to t. As for the patient's attitude towards hypertension treatment, the p-value > 0.05 means there is no relationship between family support and the attitude of hypertension sufferers. Conclusion: Family support is needed by elderly patients in hypertension management, especially medication adherence and routine blood pressure control. Health workers, especially nurses, are expected to be able to participate in efforts to empower families to improve healthcare efforts, especially elderly patients with hypertension.